2021
DOI: 10.1002/stc.2717
|View full text |Cite
|
Sign up to set email alerts
|

Optimized negative stiffness damper with flexible support for stay cables

Abstract: The negative stiffness damper (NSD) has been gaining increasing attention for cable vibration control owing to its superior energy dissipation capacity. Recent research has implied that a flexible support, rather than a rigid support, might be advantageous to improving the performance of an NSD. This study further simplifies the design of an NSD for multimode cable vibration control by leveraging the potential advantages of a flexible support. First, an equivalent model is established for the NSD support syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Optimal design of NSDs and dampers for multimode vibrations have been considered by Javanbakht et al (2018) and Javanbakht et al (2020b). When considering damper support flexibility, the effects of springs with positive and negative stiffness in series were discussed in cable vibration control (Dong and Cheng, 2021; Javanbakht et al, 2020a; Zhang et al, 2019b; Zhou et al, 2020a, 2021b). Performance of cable dampers with linear hysteretic damping, e.g., HDR dampers, can also be improved using the NSD by reducing their inherent stiffness (Sun et al, 2022c).…”
Section: Cable Multimode Vibration Mitigationmentioning
confidence: 99%
“…Optimal design of NSDs and dampers for multimode vibrations have been considered by Javanbakht et al (2018) and Javanbakht et al (2020b). When considering damper support flexibility, the effects of springs with positive and negative stiffness in series were discussed in cable vibration control (Dong and Cheng, 2021; Javanbakht et al, 2020a; Zhang et al, 2019b; Zhou et al, 2020a, 2021b). Performance of cable dampers with linear hysteretic damping, e.g., HDR dampers, can also be improved using the NSD by reducing their inherent stiffness (Sun et al, 2022c).…”
Section: Cable Multimode Vibration Mitigationmentioning
confidence: 99%
“…Chen et al [37][38][39][40] pointed out that lower support stiffness would lead to a reduced energy dissipation in viscous damping systems. However, the studies of Wang et al [19,20,41] revealed that flexible supports were advantageous in increasing the energy dissipation of the negative stiffness viscous damper systems. Therefore, a negative stiffness damping system and an amplification device can be combined to achieve a dual increase in a damper's energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, its integration with a tuned mass damper (TMD) was investigated 12,13 . Cable vibration mitigation utilizing negative stiffness elements was also conducted 14–18 . Shi et al 15 integrated negative stiffness and viscous damping to enhance cable vibration control.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Cable vibration mitigation utilizing negative stiffness elements was also conducted. [14][15][16][17][18] Shi et al 15 integrated negative stiffness and viscous damping to enhance cable vibration control. Chen et al 19 conducted a unified analysis of negative stiffness damper and inerterbased absorber for cable structures.…”
mentioning
confidence: 99%